Exposure to Early Life Adversity and Interpersonal Functioning in Attempted Suicide - Rajalin, Mia; Hirvikoski, Tatja; Renberg, Ellinor Salander; Åsberg, Marie; Jokinen, Jussi (Frontiers in Psychiatry, 2020)
Background: Early life adversity (ELA) is associated with an increased risk for mental health problems including suicidal behavior. ELA alters biological stress systems that affect behavior and control within the individual that in turn will affect interpersonal behavior. Strained relations and interpersonal conflicts leading to rejection and isolation have been shown to be factors for suicidal behavior. Difficulties in interpersonal relationships are a common reason for seeking help in psychiatric care. The aim of the present study was to examine if there are specific patterns of interpersonal problems in suicide attempters in relation to aggregation of adverse childhood experiences. Method: The study included 181 recent suicide attempters. Early life adversity was assessed by using the Karolinska Interpersonal Violence Scale. The Inventory of Interpersonal problems was used to investigate personal style in an interpersonal context. Results: Suicide attempters with high levels of early life adversity expressed a more socially avoidant, nonassertive and exploitable personal style. The results remained significant after adjustment for comorbidity with personality disorder and substance abuse. Conclusions: Suicide attempters with high levels of early life adversity tend to isolate themselves, of being introvert, and having difficulties to open up and confide in others. They report low self-confidence and self-esteem and report problems with feeling and expressing anger.These behaviors complicate interaction with others and make establishment of solid relationships more difficult. There is also a risk that suicidal communication may be missed or misinterpreted. In regards to treatment of suicidal patients, this can make it harder for suicide attempters to accept or benefit from treatment given or for professionals to provide the appropriate treatment. Clinicians should closely investigate the presence of early life adversity in suicidal patients and pay attention to their personal style and their difficulties in interpersonal exchange.